First Year Hons. Mention: A Million Yellow Birds: WRIT 1702, Becoming a Better Writer. CD: Dunja Baus. - Rana, Hassan (Jan Rehner Prize for Writing, 2023)
This personal essay endearingly conveys the writer’s connection to their culture and showcases their love of storytelling in a strong voice that immediately puts us on the same rooftop as them. The use of birds as a metaphor for kites was beautiful, and the whole piece is so highly quotable: “You see, writing is no more a choice than it is to decide what city you are born in." What an ingenious line! The essay is also wonderfully organized and creatively formatted. This is an accomplished and very impressive work.